Ecological footprint, energy usage, and economic progress relationship: the MINT countries - Kutlar, Aziz; Gulmez, Ahmet; Kabasakal, Ali; Kutlar, Selahaddin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This study explores the relationship between energy usage, per capita income, and ecological footprint as an assessment for ecological deterioration in the MINT (Mexico, Indonesia, Nigeria, Turkey) countries for the 1976-2016 period. This work estimates the long-term correlation between variables using a vector error correction model through panel vector autoregression analysis. By incorporating endogenous interactions between the variables in the system, the VAR approach addresses the endogeneity problem. Also, the impulse response functions and the effects of variables on certain lags are evaluated. Then, the cointegration between variables has been estimated with dynamic and fully modified ordinary least squares panel analysis to assess the long-term relationship further. After the examinations, a satisfactory Granger causality result of the short-term variables could not be achieved. However, the same cannot be said for long-run causality. In the impulse-response functions, the interactions of the variables on each other are evaluated. Only the increase in energy consumption, whose coefficient is statistically significant and coherent, increases the flexibility of the ecological footprint.
Keywords: Ecological degradation; economic growth; energy consumption; PVAR; ENVIRONMENTAL KUZNETS CURVE; UNIT-ROOT TESTS; CARBON-DIOXIDE EMISSIONS; CO2 EMISSIONS; PANEL-DATA; FINANCIAL DEVELOPMENT; GROWTH; CONSUMPTION; COINTEGRATION; HYPOTHESIS; Business & Economics